THE EFFECT OF HARVEST FREQUENCY AND LABOR EFFICIENCY ON THE PRODUCTIVITY OF OIL PALM ( Elaeis guineensis) Jacq.) PALM CO REGIONAL 1 RAMBUTAN GARDEN, AFDELING VIII SEI PRIOK VILLAGE - Miko Herlangga; Eka Bobby Febrianto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Palm oil productivity is the main indicator of successful plantation management in producing optimal fresh fruit bunches (FFB). This study aims to analyze the effect of harvest frequency and labor efficiency on oil palm productivity at Palm Co Regional 1 Rambutan Plantation, Afdeling VIII. This study uses a quantitative approach with descriptive and associative methods based on production theory. Secondary data for the period 2021–2025 totaling 60 observations were analyzed using multiple linear regression with the help of SPSS through the classical assumption test, t-test, F-test, and coefficient of determination. The results showed that harvest frequency had no significant effect on productivity (sig. 0.482), while labor efficiency had a positive and significant effect (sig. 0.000). Simultaneously, both variables had a significant effect on productivity with an F-count of 65.748 and an R² of 0.698. This finding confirms that increasing productivity is more effective through increasing labor efficiency through training, supervision, and continuous evaluation of harvester performance.